The Influence of World Oil Prices and Economic Growth on the Composite Stock Price Index through Foreign Exchange Rates on the Indonesia Stock Exchange - Farid, Muhammad; Yuniningsih, Yuniningsih; Handayani , Wiwik (Indonesian Journal of Advanced Research, 2024)
This study uses the foreign exchange rate to investigate how the Indonesia Stock Exchange's Composite Stock Price Index is affected by growing oil prices and economic growth. The study's population consists of all data on the Indonesia Stock currency's Composite Stock Price Index (JCI), as well as all data on foreign exchange rates, GDP, and worldwide oil prices from Bank Indonesia for the quarters ending in 2010 and 2020. The analysis technique uses path analysis which is an extension of multiple linear analysis, or path analysis is the use of regression analysis to estimate the causal relationship between variables (causal model), the population used is all composite stock price index data and the sample used is a saturated sample of all combined stock price index data. The results of the study show that the Composite Stock Price Index is influenced by the World Oil Price. There is no contribution from Economic Growth to the Composite Stock Price Index. Foreign exchange rates have an effect on the Composite Stock Price Index based on the price of oil globally. Through foreign exchange rates, economic progress affects the composite stock price index.